The Timing of Visual Object Categorization - Mack, Michael L.; Palmeri, Thomas J. (Frontiers in Psychology, 2011)
An object can be categorized at different levels of abstraction: as natural or man-made, animal or plant, bird or dog, or as a Northern Cardinal or Pyrrhuloxia. There has been growing interest in understanding how quickly categorizations at different levels are made and how the timing of those perceptual decisions changes with experience. We specifically contrast two perspectives on the timing of object categorization at different levels of abstraction. By one account, the relative timing implies a relative timing of stages of visual processing that are tied to particular levels of object categorization: Fast categorizations are fast because they precede other categorizations within the visual processing hierarchy. By another account, the relative timing reflects when perceptual features are available over time and the quality of perceptual evidence used to drive a perceptual decision process: Fast simply means fast, it does not mean first. Understanding the short-term and long-term temporal dynamics of object categorizations is key to developing computational models of visual object recognition. We briefly review a number of models of object categorization and outline how they explain the timing of visual object categorization at different levels of abstraction.